PROBLEM-BASED TEACHING IN HISTORY LESSONS - IMPLEMENTATION OF THE SYSTEM-ACTIVITY APPROACH - Alisher Kubayev, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Since history is an informational science, it is characterized by the goal of accumulating and systematizing knowledge about the past; it does not include descriptions of the components of actions, rules or theorems that would serve as the basis for cognitive activity. An action-oriented approach requires students to acquire and master historical knowledge themselves. The purpose of this article is to theoretically identify and experimentally test the effectiveness of using the technology of problem-based teaching in history lessons as a condition for the implementation of the system-activity approach.